The Principal's Role as Supervisor - Nurlinda Nurlinda (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
This study aims to describe the steps implemented by school principals as supervisors in improving the professionalism of educators of Islamic religious education subjects at SMA Negeri 1 Malili, East Luwu Regency. Examine the contribution of school principals as supervisors to increase the professionalism of educators in Islamic religious education subjects, identify the obstacles experienced, and see the principal's efforts in improving the professionalism of educators in Islamic religious education subjects. This research uses pedagogical, juridical, sociological, and normative theology approaches—data sources, primary data taken through interviews with competent parties. At the same time, secondary data is library data and school documentation that is related to research. The instrument used in collecting data is the researcher himself, who acts as a human instrument, whose function is to determine the focus of the research, select informants as data sources, collect data, assess data quality, analyze data, interpret data and draw conclusions from the findings, while the guidelines for interviews, observations, and documents as complementary instruments. The analysis used is descriptive-analytical by reducing data, presenting data, and drawing conclusions. The results of the research and analysis concluded that: 1) the steps implemented by the principal of SMA Negeri 1 Malili as a supervisor in increasing the professionalism of educators of Islamic religious education subjects were by the corridor of supervision implementation. 2) The principal as a supervisor has contributed to increasing the professionalism of educators in Islamic religious education subjects at SMA Negeri 1 Malili, East Luwu Regency. 3) The obstacles faced by the principal of SMA Negeri 1 Malili in improving the quality of PAI learning at SMA Negeri 1 Malili stem from two factors, namely internal and external factors.